An Interlaboratory Study on the Stability of All‐Printable Hole Transport Material–Free Perovskite Solar Cells - Francesca De Rossi (Energy Technology, 2020)
Comparison between different laboratories on long‐term stability analyses of perovskite solar cells (PSCs) is still lacking in the literature. This work presents the results of an inter‐laboratory study carried out between 5 laboratories from 4 countries. Carbon‐based PSCs were prepared by screen printing, encapsulated and sent to different laboratories across Europe to assess their stability by the application of three ISOS aging protocols: (a) in the dark (ISOS‐D), (b) under simulated sunlight (ISOS‐L) and (c) outdoors (ISOS‐O). Over 1000 hours stability is reported for devices in the dark, both at room temperature and at 65 °C. Under continuous illumination at open circuit, cells survived only for few hours, although they recovered after being stored in the dark. Better stability is observed for cells biased at maximum power point under illumination. Finally, devices operate in outdoors for 30 days, with minor degradation, in two different locations (Barcelona, Spain and Paola, Malta). Our findings demonstrate that open circuit conditions are too severe for stability assessment and that the diurnal variation of the PV parameters reveals performance to be strongly limited by the fill factor, in the central hours of the day, due to the high series resistance of the carbon electrode.